Sexual preference and work : a comparison between homosexual and heterosexual persons - Sandfort, Theo; Bos, H. (Utrecht: NISSO; Gay and Lesbian Studies, 1998)
"Th. Sandfort, H. Bos Fonds Suzan Daniel (FSD)"